2017
DOI: 10.1007/s12010-017-2659-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Exo-inulinase and Endo-inulinase Genes in the Oleaginous Yeast Yarrowia lipolytica for Efficient Single Cell Oil Production from Inulin

Abstract: Yarrowia lipolytica is a promising platform for the single cell oil (SCO) production. In this study, a transformant X+N8 in which exo- and endo-inulinase genes were co-expressed could produce an inulinase activity of 124.33 U/mL within 72 h. However, the inulinase activity of a transformant X2 carrying a single exo-inulinase gene was only 47.33 U/mL within 72 h. Moreover, the transformant X+N8 could accumulate 48.13% (w/w) SCO from inulin and the cell dry weight reached 13.63 g/L within 78 h, which were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…As shown in Table 1, it was found that over 88% of the intracellular fatty acids from the strain P4R5 were C 16:0 , C 18:0 , C 18:1 and C 18:2 , especially C 18:1 (35.93%). This composition was similar to those of the other oleaginous yeast lipids reported [22, 24, 25], and such yeast oils could be used as high-quality feedstock in biodiesel production that requires C 16 –C 18 fatty acids [26]. For extracellular PEFA, the GC/MS analysis indicated the presence of three major hydroxyl fatty acids of 3-OH-C 14:0 (4.40%), 3-OH-C 16:0 (70.51%) and 3-OH-C 18:0 (15.97%), in addition to a small amount of 2-hexadecenoic acid and 2-octadecenoic acid, which were probably resulted from the dehydration of the corresponding 3-hydroxyl fatty acids during the methyl esterification process (Table 1).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As shown in Table 1, it was found that over 88% of the intracellular fatty acids from the strain P4R5 were C 16:0 , C 18:0 , C 18:1 and C 18:2 , especially C 18:1 (35.93%). This composition was similar to those of the other oleaginous yeast lipids reported [22, 24, 25], and such yeast oils could be used as high-quality feedstock in biodiesel production that requires C 16 –C 18 fatty acids [26]. For extracellular PEFA, the GC/MS analysis indicated the presence of three major hydroxyl fatty acids of 3-OH-C 14:0 (4.40%), 3-OH-C 16:0 (70.51%) and 3-OH-C 18:0 (15.97%), in addition to a small amount of 2-hexadecenoic acid and 2-octadecenoic acid, which were probably resulted from the dehydration of the corresponding 3-hydroxyl fatty acids during the methyl esterification process (Table 1).…”
Section: Resultssupporting
confidence: 89%
“…In addition to glucose, inulin also has received considerable attention as a renewable and competitive non-food biomass resource for microbial lipids production by oleaginous yeasts [20, 22]. For examples, the yeast strains R. toruloides 2F5 and Pichia guilliermondii Pcla22 could produce 70.36% and 60.6% (w/w) of lipid based on cell dry weight from inulin due to their native exo-inulinase genes, respectively [24, 25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulated lipids consisted mainly of C 16:0 , C 18:1 , and C 18:2 [98]. In another study, the exo-inulase gene from K. marxianus strain KM-0 and endo-inulinase gene from Aspergillus niger strain F4 were co-expressed in Y. lipolytica strain ACA-DC 50109 [99]. The enzymes secreted from the resulting transformant (X + N8) acted synergistically to hydrolyze 90% of the inulin, with the inulinase activity reaching 136.6 U/ml in the culture medium.…”
Section: Alternative Saccharidesmentioning
confidence: 99%